El renacimiento católico en la poesía inglesa del siglo XIX - Baron, Ronald
Contiene las siguientes poesias: John Henry Newman, John Keble, Frederick WIlliam Faber, Robert Stephen HAwker, Coventry Patmore, Christina RossettiOscar WIlde, Dante Gabriel Rossetti.